A closed ecological system in a space experiment - Strauch, Sebastian; Schuster, Martin; Lebert, Michael; Richter, Peter; Schmittnägel, Martina; Häder, Donat-Peter (Life in Space for Life on Earth, 2008)
The Russian FOTON-M3 mission, a satellite for midlength experiments in space and recovery afterwards,included a closed artificial ecosystem (OMEGAHAB for Oreochromis Mossambicus-Euglena Gracilis-Aquatic HABitat) with the photosynthetic flagellate Euglena gracilis as oxygen producer and larvae of Oreochromis mossambicus, a Tilapia species, as consumer. During the 12-day orbital flight the algae were observed 10 minutes per day by means of a miniaturized microscope to analyse their swimming behavior. The fishes were also filmed to monitor their development and movement. An identical experiment was carried out as ground control. A data downlink provided the measured temperature values of he space experiment every day to readjust the temperature of the ground reference in order to eliminate the influence of the different temperature on the velocity of the development of the fishes. The system worked very well and confirmed the design in principle. OMEGAHAB was the most successful German experiment of that kind as yet.

Agrobacterium tumefaciens‐mediated nuclear transformation of a biotechnologically important microalga—euglena gracilis - Becker, Ina; Prasad, Binod; Ntefidou, Maria; Daiker, Viktor; Richter, Peter; Lebert, Michael (International Journal of Molecular Sciences, 2021)
Euglena gracilis (E. gracilis) is an attractive organism due to its evolutionary history and substantial potential to produce biochemicals of commercial importance. This study describes the establishment of an optimized protocol for the genetic transformation of E. gracilis mediated by Ag-robacterium (A. tumefaciens). E. gracilis was found to be highly sensitive to hygromycin and zeocin, thus offering a set of resistance marker genes for the selection of transformants. A. tumefaciens‐me-diated transformation (ATMT) yielded hygromycin‐resistant cells. However, hygromycin‐resistant cells hosting the gus gene (encoding β‐glucuronidase (GUS)) were found to be GUS‐negative, indi-cating that the gus gene had explicitly been silenced. To circumvent transgene silencing, GUS was expressed from the nuclear genome as transcriptional fusions with the hygromycin resistance gene (hptII) (encoding hygromycin phosphotransferase II) with the foot and mouth disease virus (FMDV)‐derived 2A self‐cleaving sequence placed between the coding sequences. ATMT of Euglena with the hptII‐2A–gus gene yielded hygromycin‐resistant, GUS‐positive cells. The transformation was verified by PCR amplification of the T‐DNA region genes, determination of GUS activity, and indirect immunofluorescence assays. Cocultivation factors optimization revealed that a higher number of transformants was obtained when A. tumefaciens LBA4404 (A600 = 1.0) and E. gracilis (A750 = 2.0) cultures were cocultured for 48 h at 19 °C in an organic medium (pH 6.5) containing 50 μM acetosyringone. Transformation efficiency of 8.26 ± 4.9% was achieved under the optimized cocul-tivation parameters. The molecular toolkits and method presented here can be used to bioengineer E. gracilis for producing high‐value products and fundamental studies.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Agrobacterium tumefaciens; Euglena gracilis; Gene silencing; Genetic engineering; Transformation

Amino acids as possible alternative nitrogen source for growth of Euglena gracilis Z in life support systems - Richter, Peter; Liu, Y.; An, Y.; Li, X.; Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Krüger, Julia; Schuster, Martin; Ntefidou, Maria; Daiker, Viktor; Haag, Ferdinand; et al. (Life Sciences in Space Research, 2015)
In recent times Euglena gracilis Z was employed as primary producer in closed environmental life-support system (CELSS), e.g. in space research. The photosynthetic unicellular flagellate is not capable of utilizing nitrate, nitrite, and urea as nitrogen source. Therefore, ammonium is supplied as an N-source in the lab (provided as diammonium-dihydrogenphosphate, (NH)HPO) to E. gracilis cultures. While nitrate exerts low toxicity to organisms, ammonium is harmful for many aquatic organisms especially, at high pH-values, which causes the ionic NH4+ (low toxicity) to be partially transformed into the highly toxic ammonia, NH. In earlier reports, Euglena gracilis was described to grow with various amino acids as sole N-source. Our aim was to investigate alternatives for (NH)HPO as N-source with lower toxicity for organisms co-cultivated with Euglena in a CELSS. The growth kinetics of Euglena gracilis cultures was determined in the presence of different amino acids (glycine, glutamine, glutamic acid, leucine, and threonine). In addition, uptake of those amino acids by the cells was measured. Cell growth in the presence of glycine and glutamine was quite comparable to the growth in (NH)HPO containing cultures while a delay in growth was observed in the presence of leucine and threonine. Unlike, aforementioned amino acids glutamate consumption was very poor. Cell density and glutamate concentration were almost unaltered throughout the experiment and the culture reached the stationary phase within 8 days. The data are compared with earlier studies in which utilization of amino acids in Euglena gracilis was investigated. All tested amino acids (glutamate with limitations) were found to have the potential of being an alternative N-source for Euglena gracilis. Hence, these amino acids can be used as a non-toxic surrogate for (NH)HPO.
Keywords: Amino-acids; CELSS; Euglena gracilis; Nitrogen source

Antimicrobial photodynamic inactivation of Pseudomonas aeruginosa persister cells and biofilms - Mahmoud, Mona; Richter, Peter; Arnold, Philipp; Lebert, Michael; Burkovski, Andreas (Photodiagnosis and Photodynamic Therapy, 2025)
Pseudomonas aeruginosa is a hard-to-treat human pathogen for which new antimicrobial agents are urgently needed. P. aeruginosa is known for forming biofilms, a complex aggregate of bacteria embedded in a self-generated protective matrix that enhance its resistance to antibiotics and the immune system. Within the biofilm, persister cells, sub-populations of slow-growing or growth-arrested cells, are associated with recalcitrance of infections and antibiotic treatment failure. Here, we investigate the influence of the anionic photosensitiser chlorophyllin (CHL)1
CRIS-Team Scopus Importer:2025-01-31
Keywords: Antimicrobial resistance; Butylparaben; Chlorophyllin; Nosocomial infection

Aquacells - Flagellates under long-term microgravity and potential usage for life support systems - Häder, Donat-Peter; Richter, Peter; Strauch, Sebastian; Schuster, Martin (Microgravity Science and Technology, 2006)
The motile behavior of the unicellular photosynthetic flagellate Euglena gracilis was studied during a two-week mission on the Russian satellite Foton M2. The precision of gravitactic orientation was high before launch and, as expected, the cells were unoriented during microgravity. While after previous short-term TEXUS flights the precision of orientation was as high as before launch, it took several hours for the organisms to regain their gravitaxis. Also the percentage of motile cells and the swimming velocity of the remaining motile cells were considerably lower than in the ground control. In preparatory experiments the flagellate Euglena was shown to produce considerable amounts of photosynthetically generated oxygen. In a coupling experiment in a prototype for a planned space mission on Foton M3, the photosynthetic producers were shown to supply sufficient amounts of oxygen to a fish compartment with 35 larval cichlids, Oreochromis mossambicus.

A successful closed aquatic ecosystem in SZ-8 mission - Li, Xiaoyan; Wang, Gaohong; Richter, Peter; Liu, Yongding; Schuster, Martin; Lebert, Michael (39th COSPAR Scientific Assembly, 2012)
Aquatic ecosystem is a useful means to explore complex interaction among different species, and data got from this kind of system can be used to re-constructer or bio-remedy damaged ecosystem or explore other planet, such as Mars. To deeply investigate interactions of different species in space environment, we established a closed aquatic ecosystem of 60 milliliter with Chlorella, Euglena and Bulinus. As a major oxygen producer, Euglena was put into the lower chamber. The initial concentration of Euglena was adjusted to 40000 cells per milliliter to avoid damage of high oxygen concentration to other organisms. As a secondary oxygen producer and food provider, Chlorella was put into the upper chamber together with 3 bulinus. The initial concentration of Chlorella was 3.2*105 cells per milliliter. After 17.5 days of duration, the system run well with 1 bulinus alive in the spaceflight group and all kept alive in the ground control.

Calcium is involved in the gravitactic orientation in colorless flagellates - Richter, Peter; Lebert, Michael; Tahedl, Harald; Häder, Donat-Peter (Journal of Plant Physiology, 2001)
The colorless flagellate Astasia longa shows a pronounced negative gravitaxis. The calcium fluorescence indicator Calcium Crimson was used to detect changes of the intracellular calcium concentration during gravitactical orientation. Astasia shows an increase of the fluorescence after a lag phase of about 10 s, a maximum after about 30 s and a decrease to the basic level within 60 s during gravitactic reorientation. The observed change in fluorescence corresponds to an almost doubling of the initial free calcium concentration. The influence of inhibitors, known to impair gravitaxis, on the calcium concentration of Astasia longa was tested. Addition of caffeine, an inhibitor of phosphodiesterase, increases, while addition of gadolinium, an inhibitor of mechanosensitive ion channels decreases the fluorescence signal. While gravitactic stimulation of caffeine-treated cells resulted in a kinetics of fluorescence intensity changes comparable to control cells the addition of gadolinium inhibited any calcium concentration change. Dynamic fluorescence imaging was used during a sounding rocket experiment (MAXUS 3 campaign). Different accelerations interrupted by μg intervals were applied to Astasia cells. The cells show an increase in the calcium signal upon acceleration and a decrease during the μg state. The results strongly reemphasize the working model of gravitaxis which is based on the activation of mechano-sensitive ion channels as one of the primary events in signal perception.
UnivIS-Import:2015-03-09:Pub.2001.nat.dbio.LBIPDH.calciu_80
Keywords: Astasia longa; Calcium; Calcium Crimson; Dynamic calcium imaging; Euglena gracilis; Gravitaxis

cAMP is involved in gravitaxis signal transduction of Euglena gracilis. - Tahedl, Harald; Richter, Peter; Lebert, Michael; Häder, Donat-Peter (Microgravity Science and Technology, 1999)
UnivIS-Import:2015-03-05:Pub.1999.nat.dbio.LBIPDH.campis

Changes in Gravitaxis and Gene-Expression in an Euglena gracilis Culture over Time - Krüger, Julia; Richter, Peter; Stoltze, Julia; Prasad, Binod; Strauch, Sebastian; Krüger, Marcus; Nasir, Adeel; Lebert, Michael (Biomolecules, 2024)
Age-dependent changes in the transcription levels of 5-day-old Euglena gracilis cells, which showed positive gravitaxis, 6-day-old cells without gravitactic orientation, and older cells (9- and 11-day-old, which displayed a precise negative gravitaxis) were determined through microarray analysis. Hierarchical clustering of four independent cell cultures revealed pronounced similarities in transcription levels at the same culture age, which proves the reproducibility of the cultivation method. Employing the non-oriented cells from the 6-day-old culture as a reference, about 2779 transcripts were found to be differentially expressed. While positively gravitactic cells (5-day-old culture) showed only minor differences in gene expression compared to the 6-day reference, pronounced changes of mRNAs (mainly an increase) were found in older cells compared to the reference culture. Among others, genes coding for adenylyl cyclases, photosynthesis, and metabolic enzymes were identified to be differentially expressed. The investigated cells were grown in batch cultures, so variations in transcription levels most likely account for factors such as nutrient depletion in the medium and self-shading. Based on these findings, a particular transcript (e.g., transcript 19556) was downregulated using the RNA interference technique. Gravitaxis and phototaxis were impaired in the transformants, indicating the role of this transcript in signal transduction. Results of the experiment are discussed regarding the increasing importance of E. gracilis in biotechnology as a source of valuable products and the possible application of E. gracilis in life-support systems.
CRIS-Team Scopus Importer:2024-04-05
Keywords: culture age; Euglena gracilis; gravitaxis; microarray analysis; phototaxis

Changes of Gene Expression in Euglena gracilis Obtained During the 29th DLR Parabolic Flight Campaign - Krüger, Julia; Richter, Peter; Stoltze, Julia; Strauch, Sebastian; Krüger, Marcus; Daiker, Viktor; Prasad, Binod; Sonnewald, Sophia; Reid, Stephen; Lebert, Michael (Scientific Reports, 2019)
Parabolic flight maneuvers of Novespace's Airbus A310 ZERO-G produce subsequent phases of hypergravity (about 20 s), microgravity (about 22 s) and another 20 s hypergravity on experiments located in the experiment area of the aircraft. The 29th DLR parabolic flight campaign consisted of four consecutive flight days with thirty-one parabolas each day. Euglena gracilis cells were fixed with TRIzol during different acceleration conditions at the first and the last parabola of each flight. Samples were collected and analyzed with microarrays for one-color gene expression analysis. The data indicate significant changes in gene expression in E. gracilis within short time. Hierarchical clustering shows that changes induced by the different accelerations yield reproducible effects at independent flight days. Transcription differed between the first and last parabolas indicating adaptation effects in the course of the flight. Different gene groups were found to be affected in different phases of the parabolic flight, among others, genes involved in signal transduction, calcium signaling, transport mechanisms, metabolic pathways, and stress-response as well as membrane and cytoskeletal proteins. In addition, transcripts of other areas, e.g., DNA and protein modification, were altered. The study contributes to the understanding of short-term effects of microgravity and different accelerations on cells at a molecular level.
CRIS-Team Scopus Importer:2019-10-15

Corrigendum to “Antimicrobial Photodynamic Inactivation of Pseudomonas aeruginosa Persister Cells and Biofilms” [Photodiagnosis and Photodynamic Therapy 51 (2025) 104456] (Photodiagnosis and Photodynamic Therapy (2025) 51, (S1572100024004927), (10.1016/j.pdpdt.2024.104456)) - Mahmoud, Mona; Richter, Peter; Arnold, Philipp; Lebert, Michael; Burkovski, Andreas (Photodiagnosis and Photodynamic Therapy, 2025)
The authors regret <1. In the discussion section: The current text states: "These channels, which are non-specific and passive transporters of small molecules, are located on the cell membrane [[42], [43]]. The antimicrobial effects of paraben increases as the alkyl chain length of the ester group increases [32,34]." The correct references should be as highlighted: "These channels, which are non-specific and passive transporters of small molecules, are located on the cell membrane [42]. The antimicrobial effects of paraben increases as the alkyl chain length of the ester group increases [41,43]”>. The authors would like to apologise for any inconvenience caused. Additionally, Fig. 11 appears unorganized in the published article and it should appear as in the following image to ensure clarity:
CRIS-Team Scopus Importer:2025-02-28

Current Knowledge about the Impact of Microgravity on Gene Regulation - Corydon, Thomas J.; Schulz, Herbert; Richter, Peter; Strauch, Sebastian M.; Böhmer, Maik; Ricciardi, Dario A.; Wehland, Markus; Krüger, Marcus; Erzinger, Gilmar S.; Lebert, Michael; Infanger, Manfred; Wise, Petra M.; et al. (Cells, 2023)
Microgravity (µg) has a massive impact on the health of space explorers. Microgravity changes the proliferation, differentiation, and growth of cells. As crewed spaceflights into deep space are being planned along with the commercialization of space travelling, researchers have focused on gene regulation in cells and organisms exposed to real (r-) and simulated (s-) µg. In particular, cancer and metastasis research benefits from the findings obtained under µg conditions. Gene regulation is a key factor in a cell or an organism's ability to sustain life and respond to environmental changes. It is a universal process to control the amount, location, and timing in which genes are expressed. In this review, we provide an overview of µg-induced changes in the numerous mechanisms involved in gene regulation, including regulatory proteins, microRNAs, and the chemical modification of DNA. In particular, we discuss the current knowledge about the impact of microgravity on gene regulation in different types of bacteria, protists, fungi, animals, humans, and cells with a focus on the brain, eye, endothelium, immune system, cartilage, muscle, bone, and various cancers as well as recent findings in plants. Importantly, the obtained data clearly imply that µg experiments can support translational medicine on Earth.
CRIS-Team Scopus Importer:2023-04-21
Keywords: cancer; cells; gene expression; gene regulation; microgravity; microorganisms; plants; space

Current knowledge about the impact of microgravity on the proteome - Strauch, Sebastian; Grimm, Daniela; Corydon, Thomas J.; Krueger, Marcus; Bauer, Johann; Lebert, Michael; Wise, Petra; Infanger, Manfred; Richter, Peter (Expert Review of Proteomics, 2019)
Introduction: Microgravity (mu g) is an extreme stressor for plants, animals, and humans and influences biological systems. Humans in space experience various health problems during and after a long-term stay in orbit. Various studies have demonstrated structural alterations and molecular biological changes within the cellular milieu of plants, bacteria, microorganisms, animals, and cells. These data were obtained by proteomics investigations applied in gravitational biology to elucidate changes in the proteome occurring when cells or organisms were exposed to real mu g (r-mu g) and simulated mu g (s-mu g). Areas covered: In this review, we summarize the current knowledge about the impact of mu g on the proteome in plants, animals, and human cells. The literature suggests that mu g impacts the proteome and thus various biological processes such as angiogenesis, apoptosis, cell adhesion, cytoskeleton, extracellular matrix proteins, migration, proliferation, stress response, and signal transduction. The changes in cellular function depend on the respective cell type. Expert commentary: This data is important for the topics of gravitational biology, tissue engineering, cancer research, and translational regenerative medicine. Moreover, it may provide new ideas for countermeasures to protect the health of future space travelers.
Keywords: Proteome; mass spectrometry; plants; human cells; tissue engineering; cancer

Delayed fluorescence, steady state fluorescence, photosystem II quantum yield as endpoints for toxicity evaluation of Cu2+ and Ag+ - Strauch, Sebastian; Richter, Peter; Haag, Ferdinand; Krüger, Marcus; Krüger, Julia; Azizullah, Azizullah; Breiter, Roman; Lebert, Michael (Environmental and Experimental Botany, 2016)
The effect of copper and silver ions on photosynthetic parameters of the flagellate Euglena gracilis was determined. The photosystem II quantum yield (Y) and steady state fluorescence (F) were measured with a PAM-fluorometer, while delayed fluorescence (DF) was determined by means of a sensitive single-photon camera attached to an image analysis device, which counted the relative number of photons released from the algae in darkness after previous light-stimulation. We found that after 3 h of incubation photosynthesis was affected only in the presence of relatively high concentrations of the used noble metals. The obtained EC values for Cu were 505.8 mg L (Y ), 286.5 mg L (DF), and 491.0 mg L (F). The EC values for silver ions were 51.9 mg L (Y ), 51.8 mg L (DF) (values for F not determinable). Photosynthesis is far less sensitive against toxic noble metals compared to motility parameters as reported in earlier studies, in part because the organelles of photosynthesis, the chloroplasts, are well protected from external substances within the cell, while flagella, reaching into the surrounding of the cell, are more easily influenced. As chloroplasts are easily accessible by means of non-invasive methods e.g. PAM- fluorometry, they are probably interesting model systems in order to detect effects of substances deep inside the cell. Influence on the chloroplasts is a measure that a germicide entered the cells, diffused through the cytoplasm and the membranous systems and reached compartmentalized enzyme complexes.
Keywords: Delayed fluorescence; Ecotoxicology; Euglena gracilis; PAM-fluorometry; Photosynthetic yield; Steady state fluorescence

Disproval of the Starch-Amyloplast Hypothesis? - Richter, Peter; Strauch, Sebastian; Lebert, Michael (Trends in Plant Science, 2019)
In a recent publication, Edelmann (Protoplasma 2018; 255,1877-1881) refuted the well-established starch-amyloplast hypothesis of gravitropism in plants. Gravitropic curvatures of shoots and roots were still present after amyloplast- containing tissues (in sheath of vascular bundles and root caps) were dissected. Here, we discuss Edelmann's data in the light of Popper's falsification principle.
CRIS-Team WoS Importer:2019-04-02

Diurnal stratification of oxygen in shallow aquaculture ponds in central Europe and recommendations for optimal aeration - Oberle, Martin; Salomon, Sebastian; Ehrmaier, Bruno; Richter, Peter; Lebert, Michael; Strauch, Sebastian (Aquaculture, 2019)
Keywords: Hypoxia; Thermal stratification; Aeration; Cyprinus carpio

ECOTOX - Biomonitoring based on real time movement analysis of unicellular organisms - Streb, Christine; Richter, Peter; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (18TH ESA SYMPOSIUM ON EUROPEAN ROCKET AND BALLOON PROGRAMMES AND RELATED RESEARCH, 2002)
To meet the todays needs for the protection of the environment from pollution through cumulative poisonings or biohazards ecotoxicology uses biotests, to determine effects of chemicals and sewage waters to ecosystems. ECOTOX is a biotest system that allows both the estimation of risks arising from certain substances or substance mixtures as well as the on-line monitoring of waste waters and aquatic ecosystems. Euglena gracilis, the employed organism for freshwater measurements, found to be highly sensitive to external factors, provides several physiological endpoints, well fitted for toxicity hazard assessment in water management, which can be characterized by the ECOTOX program.

Effects of increased salinity on gravitaxis in Euglena gracilis - Richter, Peter; Börnig, Anke; Streb, Christine; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (Journal of Plant Physiology, 2003)
The unicellular freshwater flagellate Euglena gracilis regulates its position in the water column by means of phototactic and gravitactic behavior. Recent experiments have revealed that the cells switch between negative and positive gravitaxis depending upon environmental stimuli such as solar radiation. In this study, the effect of increased salinity on gravitaxis in Euglena gracilis was investigated. In some experiments it was found that salt concentrations up to 5 g L-1 (in some experiments 10 g L-1) increased the motility, velocity and precision of negative gravitactic orientation. Higher salt concentrations decreased all these parameters. At concentrations of about 15 g L-1, cells which did not become immobile, switched from negative to positive gravitaxis. Positive gravitaxis persisted for several hours or even days when the cells were transferred back to standard culture medium. Most of the cells in cultures exposed to salt concentrations above 20g L-1 lost their motility (partial formation of palmella stages) but recovered when transferred back to standard medium or de-ionised water. Post recovery, the cells showed pronounced positive gravitaxis. Additional investigations on the pigmentation, revealed that the cells showed a complete loss of a carotenoid shoulder in the spectrum, which reappeared when the cells were brought back to standard medium.
Keywords: salinity; Euglena gracilis; flagellates; gravitaxis; pigmentation

Enhanced photosynthetic activity in Spinacia oleracea by spectral modification with a photoluminescent light converting material - Xia, Qi; Batentschuk, Miroslaw; Osvet, Andres; Richter, Peter; Häder, Donat-Peter; Schneider, Juergen; Brabec, Christoph; Wondraczek, Lothar; Winnacker, Albrecht (Optics Express, 2013)
The spectral conversion of incident sunlight by appropriate photoluminescent materials has been a widely studied issue for improving the efficiency of photovoltaic solar energy harvesting. By using phosphors with suitable excitation/emission properties, also the light conditions for plants can be adjusted to match the absorption spectra of chlorophyll dyes, in this way increasing the photosynthetic activity of the plant. Here, we report on the application of this principle to a high plant, Spinacia oleracea. We employ a calcium strontium sulfide phosphor doped with divalent europium (Ca0.4Sr0.6S:Eu2+, CSSE) on a backlight conversion foil in photosynthesis experiments. We show that this phosphor can be used to effectively convert green to red light, centering at a wavelength of 650 nm which overlaps the absorption peaks of chlorophyll a/b pigments. A measurement system was developed to monitor the photosynthetic activity, expressed as the CO2 assimilation rate of spinach leaves under various controlled light conditions. Results show that under identical external light supply which is rich in green photons, the CO2 assimilation rate can be enhanced by more than 25% when the actinic light is modified by the CSSE conversion foil as compared to a purely reflecting reference foil. These results show that the phosphor could be potentially applied to modify the solar spectrum by converting the green photons into photosynthetically active red photons for improved photosynthetic activity. © 2013 Optical Society of Americ
Keywords: Engineering controlled terms: Carbon dioxide; Light emission; Phosphors; Photons; Plants (botany); Solar energy; Calcium Assimilation rate; Measurement system; Photoluminescent materials; Photosynthetic activity; Photovoltaic solar energy; Spectral conversion; Spectral modifications; Strontium sulfide phosphor; Divalent europium Engineering main heading: Light EMTREE drug terms: carbon dioxide; strontium EMTREE medical terms: article; chemistry; luminescence; metabolism; photon; photosynthesis; physiology; spectrofluorometry; spinach; time MeSH: Carbon Dioxide; Luminescence; Photons; Photosynthesis; Spectrometry; Fluorescence; Spinacia oleracea; Strontium; Time Factors Medline is the source for the MeSH terms of this document.

Euglena gracilis as a promising eukaryotic model system for fast detection of high pressure induced cell destruction - Stoltze, Julia; Izydor, Marika; Hainthaler, Markus; Richter, Peter; Schlücker, Eberhard; Lebert, Michael (Environmental and Experimental Botany, 2017)
High hydrostatic pressure (HHP) is a promising method for the inactivation of cells and enzymes in many applications (e.g. food industry, pharmaceutical industry, chemistry). The effects of various high-hydrostatic pressures (20 MPa, 50 MPa, 55 MPa, 60 MPa, 75 MPa, 100 MPa, 150 MPa, 200 MPa, 400 MPa) on the unicellular flagellate Euglena gracilis were determined: (a) life/dead staining with ethidium bromide (EtBr), (b) loss of flagellum, (c) movement behavior, (d) recovery after 7 d, (e) photosystem II quantum yield (Y(PSII)). Pressure was applied for 300 s at room temperature (pressure increment and decrement: 10 MPa s). The EC value of vitality (EtBr-positive cells) directly after pressure application was 109 MPa. Cell vitality was not impaired below 100 MPa. No recovery of cells after 7 d-cultivation in fresh medium was observed after pressure treatment above 100 MPa. Flagellum-based free swimming of cells was already impaired at pressures above 50 MPa, where some cells started metabolic movement behavior. From 75 MPa to 100 MPa all cells moved metabolically, while at higher-pressure all cells became immotile. In the pressure range between 75 MPa and 200 MPa, cells lost their flagellum. Interestingly, cells pressurized with 400 MPa retained their flagella. Directly after HHP-treatment EC of Y(PSII)-inhibition was about 101 MPa, after 6 h about 102 MPa. The use of fluorescence-based methods is considerably fast, easy and reliable. Because of the different easily recordable parameters, we believe that Euglena gracilis is a promising test organism to determine HHP-effects on eukaryotes. The effects on photosynthesis indicate impacts on intracellular membrane and protein complexes.
Keywords: Euglena gracilis; Flagellum; High pressure induced cell destruction; High-hydrostatic pressure (HHP); Motility; PAM-fluorimetry

Evaluation of the adverse effects of two commonly used fertilizers, DAP and urea, on motility and orientation of the green flagellate Euglena gracilis - Azizullah, Azizullah; Nasir, Adeel; Richter, Peter; Lebert, Michael; Häder, Donat-Peter (Environmental and Experimental Botany, 2011)
The effect of two commonly used fertilizers, DAP (diammonium phosphate) and urea was studied on the freshwater flagellate Euglena gracilis using the automatic biotest ECOTOX. NOEC and EC(50) values for various parameters like motility, velocity, cell shape and gravitaxis were calculated. The NOEC and EC(50) values obtained for DAP were much lower than those for urea; i.e. DAP showed a stronger inhibitory effect as compared to urea. The inhibition caused by DAP increased with increasing exposure time over 24 h but urea showed no augmentation with increasing exposure time. Application of DAP resulted in an increased pH and high concentrations of ammonia but urea did neither affect the pH nor affect the ammonia concentration. Recovery experiments in deionized water after urea application showed a reconstitution of motility after 72 h. After an application of 1.35 g L(-1) (24 h EC(50) for motility) DAP motility recovered after 72 h but motility did not recover when the concentration was doubled (2.7 g L-1). The EC(50) values obtained were compared with the EC(50)/LC(50) values reported for other aquatic organisms and were found to be comparable with the reported values. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: DAP; Urea; ECOTOX; Euglena gracilis; Motility; Gravitaxis

Exploration of space to achieve scientific breakthroughs - Prasad, Binod; Richter, Peter; Vadakedath, Nithya; Mancinelli, Rocco; Krüger, Marcus; Strauch, Sebastian M.; Grimm, Daniela; Darriet, Philippe; Chapel, Jean Paul; Cohen, Jacob; Lebert, Michael (Biotechnology Advances, 2020)
Living organisms adapt to changing environments using their amazing flexibility to remodel themselves by a process called evolution. Environmental stress causes selective pressure and is associated with genetic and phenotypic shifts for better modifications, maintenance, and functioning of organismal systems. The natural evolution process can be used in complement to rational strain engineering for the development of desired traits or phenotypes as well as for the production of novel biomaterials through the imposition of one or more selective pressures. Space provides a unique environment of stressors (e.g., weightlessness and high radiation) that organisms have never experienced on Earth. Cells in the outer space reorganize and develop or activate a range of molecular responses that lead to changes in cellular properties. Exposure of cells to the outer space will lead to the development of novel variants more efficiently than on Earth. For instance, natural crop varieties can be generated with higher nutrition value, yield, and improved features, such as resistance against high and low temperatures, salt stress, and microbial and pest attacks. The review summarizes the literature on the parameters of outer space that affect the growth and behavior of cells and organisms as well as complex colloidal systems. We illustrate an understanding of gravity-related basic biological mechanisms and enlighten the possibility to explore the outer space environment for application-oriented aspects. This will stimulate biological research in the pursuit of innovative approaches for the future of agriculture and health on Earth.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Cancer research; Colloids; Epigenetics; Evolution; Horizontal gene transfer; Microgravity; Mutation; Space; Stress response; Tissue engineering

Flagellates as model system for gravity detection of single cells - Lebert, Michael; Richter, Peter; Daiker, Viktor; Schuster, Martin; Tebart, Jennifer; Strauch, Sebastian; Häder, Donat-Peter (38th COSPAR Scientific Assembly, 2010)
Euglena gracilis is a unicellular, photosynthetic organism which uses light and gravity as en-vironmental hints to reach and stay in horizons of the water column which are optimal for growth and reproduction. The orientation in respect to light (so called positive and nega-tive phototaxis, i.e. movement toward or away of a light source) was well known and fairly good understood. In contrast, knowledge about the movement away from the centre of gravity (negative gravitaxis) was rather scarce. Over a century it was unclear whether orientation in respect to the gravity vector is based on a physical or a physiological mechanism. Recent results clearly favour the latter. Knock-down mutants (RNAi) were characterized which define certain key components of the gravitactic signal transduction chain. These key components include a TRP-like channel, a gravitaxis-specific calmodulin and a protein kinase A. The molecular characterization of these components is currently performed and will be presented. Euglena is not only a model system for the close understanding of gravity detection in single cells, but can also be used as photosynthetic component, i.e. oxygen source and carbon dioxide as well as nitrogenic components sink in Closed Environmental Systems (CES). Due CES are systems of choice in times of scarce flight opportunities. They allow a massive sample sharing and combine possibilities to do microgravity research for biologists but also for engineers, physicists and material scientists. Recent attempts include Aquacells and Omegahab. In the near future miniaturized systems (Chinese ShenZhou) as well as advanced CES will be flown or tested, respectively. Current attempts and plans will be presented.

Gravi-sensing microorganisms as model systems for gravity sensing in eukaryotes - Streb, Christine; Richter, Peter; Lebert, Michael; Häder, Donat-Peter (Exo-/astro-biology. Proceedings of the First European Workshop, 2001)
Gravisensing in single cells and multicellular organisms is a very active field of investigation. Similarities between gravity sensing mechanisms in uni- and multicellular eukaryotes make single cells ideal model systems for the understanding of gravity responses on the cellular and molecular level with far fetching significance for other systems. This article gives a short overview about gravisensing in plants (Arabidopsis, Chara) aswell as the ciliates Loxodes and Paramecium and concentrates on gravitaxis research in the single cellular flagellate, Euglena gracilis. Experiments revealed the involvement of CAMP, Ca2+ specific mechanosensitive channels and membrane potential in the signal transduction chain of gravitaxis. Future perspectives for the use of motile, photosynthetic and other unicellular microorganisms for space applications e.g. for oxygen supply in life support systems or research on the origin of life are discussed.

Gravitactic signal transduction elements in Astasia longa investigated during parabolic flights - Richter, Peter; Schuster, Martin; Lebert, Michael; Häder, Donat-Peter (Microgravity Science and Technology, 2003)
Euglena gracilis and its close relative Astasia longa show a pronounced negative gravitactic behavior. Many experiments revealed that gravitaxis is most likely mediated by an active physiological mechanism. The goal of the present study was to examine elements in the sensory transduction by means of inhibitors of gravitaxis and the intracellular calcium concentration during short microgravity periods. During the course of six parabolic flights (ESA 31(th) parabolic flight campaign and DLR 6(th) parabolic flight campaign) the effects of trifluoperazine (calmodulin inhibitor), caffeine (phosphodiesterase inhibitor) and gadolinium (blocks mechano-sensitive ion channels) was investigated Due to the extreme parabolic flight maneuvers of the aircraft alternating phases of 1.8 x g(n) (about 20 s) and microgravity (about 22 s) were achieved (g(n): acceleration of Earth's gravity field). The duration of the microgravity periods was sufficient to detect a loss of cell orientation in the samples. In the presence of gadolinium impaired gravitaxis was found during acceleration, while caffeine-treated cells showed, compared to the controls, a very precise gravitaxis and faster reorientation in the 1.8 x g(n) period following microgravity. A transient increase of the intracellular calcium upon increased acceleration was detected also in inhibitor-treated samples. Additionally, it was found that the cells showed a higher calcium signal when they deviated from the vertical swimming direction. In the presence of trifluoperazine a slightly higher general calcium signal was detected compared to untreated controls, while gadolinium was found to decrease the intracellular calcium concentration. In the presence of caffeine no clear changes of intracellular calcium were detected compared to the control.

Gravitational sensory transduction chain in flagellates - Häder, Donat-Peter; Richter, Peter; Ntefidou, Maria; Lebert, Michael (Advances in Space Research, 2005)
Earlier hypotheses have assumed that gravitactic orientation in flagellates, such as the photosynthetic unicell Euglena gracilis, is brought about by passive alignment of the cells in the water Column by being tail heavy. A recent experiment on a sounding rocket (TEXUS 40) comparing immobilized cells with mobile cells demonstrated that the passive buoy effect can account for approximately 20% of the orientation of the cells in a gravity field. The cells show either positive or negative gravitaxis depending oil other external or internal factors. Shortly after inoculation, the tendency of young cells to swim downward in the water Column can be readily reverted by adding micromolar concentrations of some heavy metal ions including copper, cadmium or lead. The negative gravitaxis of older cells is converted into a positive one by stress factors Such as increasing salinity or exposure to excessive visible or UV radiation. The mechanism for this switch seems to involve reactive oxygen species since the gravitactic sign change was Suppressed when oxygen was removed by flushing the cell suspension with nitrogen. Also, the addition of radical scavengers (Trolox, ascorbic acid or potassium cyanide) abolished or reduced the gravitactic sign change. Addition of hydrogen peroxide induced a gravitactic sign change in the absence of external stress factors. The primary reception for the gravity vector seems to involve mechanosensitive ion channels which specifically gate calcium ions inward. We have identified several gene sequences for putative mechanosensory channels in Euglena and have applied RNAi to identify which of these channels are involved in graviperception. The influx of Ca2+ activates calmodulin (CaM) which has been shown to be involved in the sensory transduction chain of graviorientation. It is known that an adenylyl cyclase is bound to the flagellar membrane in Euglena which is activated by CaM. This enzyme produces cAMP which has also been shown to be the key messenger in phototaxis in the same organism by mediating flagellar reorientation and thus swimming path Course correction. (c) 2005 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Euglena; gravitaxis; flagellate; graviperception; mechanosensitive ion channels

Gravitaxis and graviperception in flagellates and ciliates. - Häder, Donat-Peter; Lebert, Michael; Richter, Peter (Proceedings 14th ESA Symposium on European Rocket and Balloon Programmes and Related Research., 1999)
UnivIS-Import:2015-04-16:Pub.1999.nat.dbio.LBIPDH.gravit

Gravitaxis of Euglena gracilis depends only partially on passive buoyancy - Richter, Peter; Schuster, Martin; Lebert, Michael; Streb, Christine; Häder, Donat-Peter (Advances in Space Research, 2007)
In darkness, the unicellular freshwater flagellate Euglena gracilis shows a pronounced negative gravitactic behavior, and the cells swim actively upward in the water column. Up to now it was unclear whether this behavior is based on a passive (physical) alignment mechanism (e.g., buoyancy due to a fore-aft asymmetry of the cell body) or on an active physiological mechanism. A sounding rocket experiment was performed in which the effect of sub-1g-accelerations (0.05, 0.08, 0.12, and 0.2g) on untreated living cells and immobilized (fixation with liquid nitrogen) cells was observed. By means of computerized image analysis the angles of the cells long axis with respect to the acceleration vector were analyzed in order to calculate and compare the reorientation kinetics of the immobilized cells versus that of the controls. In both groups, the reorientation kinetics depended on the dose, but the reorientation of the living cells was about five times faster than that of the immobilized cells. This indicates that in young cells gravitaxis can be explained by a physical mechanism only to a small extend. In older cultures, in which the cells often have a drop shaped cell body, the physical reorientation is considerably faster, and a more pronounced influence of passive alignment caused by fore/aft asymmetry (drag-gravity model) can not be excluded. In addition to these results, Euglena gracilis cells seem to respond very sensitively to small accelerations when they are applied after a longer microgravity period. The data indicate that gravitactic orientation occurred at an acceleration as low as 0.05g. (C) 2006 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Euglena gracilis; gravitaxis; motion analysis; sounding rockets; fore/aft asymmetry; buoyancy

High light exposure leads to a sign change in gravitaxis of the flagellate Euglena gracilis - Ntefidou, Maria; Richter, Peter; Streb, Christine; Lebert, Michael; Häder, Donat-Peter (18TH ESA SYMPOSIUM ON EUROPEAN ROCKET AND BALLOON PROGRAMMES AND RELATED RESEARCH, 2002)
In the absence of other external stimuli the motile, unicellular freshwater flagellate Euglena gracilis normally swims upward in the water column (negative gravitaxis). This behavior is most likely triggered by active physiological orientation mechanisms. Recently it was found that negative gravitaxis often inverts to a positive one upon high light exposure. This response is not mediated by the photoreceptor (the paraxonemal body - PAB), because PAB-free mutants do also show this response after high radiation. It is very likely that the phenomenon is triggered by reactive oxygen species, because in the absence of oxygen no gravitaxis sign change was observed. Also increased salinity inverses the sign of gravitaxis, leading to the assumption that environmental stressors induce the formation of reactive oxygen species, serving as signal molecules.

High light exposure leads to a sign change of gravitaxis in the flagellate Euglena gracilis - Richter, Peter; Ntefidou, Maria; Streb, Christine; Faddoul, Jaoudat; Lebert, Michael; Häder, Donat-Peter (Acta Protozoologica, 2002)
The unicellular flagellate Euglena gracilis orients itself in the water column by means of pronounced phototaxis and gravitaxis. The antagonism of phototaxis and gravitaxis brings the cells in a position in the water column providing them with optimal light conditions for their photosynthetic apparatus (about 30 Wm(-2)). Long exposure to solar or artificial radiation induces a loss of the negative gravitactic orientation in Euglena gracilis or very often a pronounced, persistent (>4h) sign change in gravitaxis. The effects on gravitaxis are exclusively due to UV and intensive blue light as experiments with different light qualities revealed. This phenomenon is not caused by the phototaxis photoreceptor or chloroplast processes, because also the colorless and blind (no photoreceptor) Euglena gracilis If mutant and Astasia longa reverse the sign of gravitaxis upon strong radiation. The sign change is oxygen-dependent, because gravitaxis is not affected in oxygen free medium (in wild type Euglena gracilis, as well as in the If mutant and Astasia longa). This indicates the involvement of oxygen radicals as a trigger of gravitaxis sign reversal. As the destruction of the photoreceptor molecules by light leads to a loss of phototaxis, the switch from. negative to positive gravitaxis might be an adaptation mechanism of the cells to escape from deleterious radiation even after loss of the ability to perceive the light direction.
Keywords: Astasia longa; Euglena gracilis; gravitaxis; oxygen; phototaxis; sign change; solar radiation; UV

High light-induced sign change of gravitaxis in the flagellate Euglena gracilis is mediated by reactive oxygen species - Richter, Peter; Streb, Christine; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (Acta Protozoologica, 2003)
Euglena gracilis responds to abiotic stress factors (high light, salinity, heavy metals) with a sign change of its gravitactic behavior. This phenomenon is oxygen dependent and can be suppressed by the application of the reductant dithionite. It is not mediated by the photoreceptor since also blind mutants change their movement behavior upon high light exposure. It is also not mediated by the chloroplasts since the gravitactic sign change was also found in white, chloroplast-free mutants. The NO radical donor SNAP and the NO cleaver carboxy-PTIO had no obvious effects on gravitaxis or gravitactic sign change, respectively, indicating that NO radicals are not likely involved in gravitactic sign change. Gravitactic sign change was suppressed when oxygen was removed by flushing the cell suspension with nitrogen. Also, the addition of the radical scavengers Trolox, ascorbic acid or potassium cyanide abolished or reduced gravitactic sign change. Quantification of reactive oxygen species (ROS) in the cells indicated that these treatments reduced the evolution of ROS. Furthermore, addition of hydrogen peroxide induced gravitactic sign change in the absence of external stress factors. These results indicate that gravitactic sign change is triggered by ROS (most likely hydrogen peroxide) which are probably produced by cytochrome-c-oxidase in the mitochondria. The clear responses of Euglena to abiotic stress factors suggest that these cells are probably interesting model systems in the study of stress signaling.
Keywords: Euglena gracilis; gravitaxis; hydrogen peroxide; reactive oxygen species; sign change; UV

How and why does the proteome respond to microgravity? - Grimm, Daniela; Wise, Petra; Lebert, Michael; Richter, Peter; Baatout, Sarah (Expert Review of Proteomics, 2011)
For medical and biotechnological reasons, it is important to study mammalian cells, animals, bacteria and plants exposed to simulated and real microgravity. It is necessary to detect the cellular changes that cause the medical problems often observed in astronauts, cosmonauts or animals returning from prolonged space missions. In order for in vitro tissue engineering under microgravity conditions to succeed, the features of the cell that change need to be known. In this article, we summarize current knowledge about the effects of microgravity on the proteome in different cell types. Many studies suggest that the effects of microgravity on major cell functions depend on the responding cell type. Here, we discuss and speculate how and why the proteome responds to microgravity, focusing on proteomic discoveries and their future potential.
Keywords: apoptosis; Arabidopsis thaliana; bacteria; cytoskeleton; growth; human cells; microgravity; proteomics; tissue engineering

How the space environment influences organisms: An astrobiological perspective and review - Prasad, Binod; Richter, Peter; Vadakedath, Nithya; Haag, Ferdinand; Strauch, Sebastian M.; Mancinelli, Rocco; Schwarzwälder, Achim; Etcheparre, Emmanuel; Gaume, Nicolas; Lebert, Michael (International Journal of Astrobiology, 2021)
The unique environment of space is characterized by several stress factors, including intense radiation, microgravity, high vacuum and extreme temperatures, among others. These stress conditions individually or in-combination influence genetics and gene regulation and bring potential evolutionary changes in organisms that would not occur under the Earth's gravity regime (1 × g). Thus, space can be explored to support the emergence of new varieties of microbes and plants, that when selected for, can exhibit increased growth and yield, improved resistance to pathogens, enhanced tolerance to drought, low nutrient and disease, produce new metabolites and others. These properties may be more difficult to achieve using other approaches under 1 × g. This review provides an overview of the space microgravity and ionizing radiation conditions that significantly influence organisms. Changes in the genomics, physiology, phenotype, growth and metabolites of organisms in real and simulated microgravity and radiation conditions are illustrated. Results of space biological experiments show that the space environment has significant scientific, technological and commercial potential. Combined these potentials can help address the future of life on Earth, part of goal e of astrobiology.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Agricultural plants; evolution; microgravity; radiation; space; space-breeding; stress-induced mutation

Impact of a High Magnetic Field on the Orientation of Gravitactic Unicellular Organisms-A Critical Consideration about the Application of Magnetic Fields to Mimic Functional Weightlessness - Hemmersbach, Ruth; Simon, Anja; Wasser, Kai; Hauslage, Jens; Christianen, Peter C. M.; Albers, Peter W.; Lebert, Michael; Richter, Peter; Alt, Wolfgang; Anken, Ralf (Astrobiology, 2014)
The gravity-dependent behavior of Paramecium biaurelia and Euglena gracilis have previously been studied on ground and in real microgravity. To validate whether high magnetic field exposure indeed provides a ground-based facility to mimic functional weightlessness, as has been suggested earlier, both cell types were observed during exposure in a strong homogeneous magnetic field (up to 30 T) and a strong magnetic field gradient. While swimming, Paramecium cells were aligned along the magnetic field lines; orientation of Euglena was perpendicular, demonstrating that the magnetic field determines the orientation and thus prevents the organisms from the random swimming known to occur in real microgravity. Exposing Astasia longa, a flagellate that is closely related to Euglena but lacks chloroplasts and the photoreceptor, as well as the chloroplast-free mutant E. gracilis 1F, to a high magnetic field revealed no reorientation to the perpendicular direction as in the case of wild-type E. gracilis, indicating the existence of an anisotropic structure (chloroplasts) that determines the direction of passive orientation. Immobilized Euglena and Paramecium cells could not be levitated even in the highest available magnetic field gradient as sedimentation persisted with little impact of the field on the sedimentation velocities. We conclude that magnetic fields are not suited as a microgravity simulation for gravitactic unicellular organisms due to the strong effect of the magnetic field itself, which masks the effects known from experiments in real microgravity. Key Words: Levitation-Microgravity-Gravitaxis-Gravikinesis-Gravity. Astrobiology 14, 205-215.

Indications for acceleration-dependent changes of membrane potential in the flagellate Euglena gracilis - Richter, Peter; Schuster, Martin; Meyer, Irmin; Lebert, Michael; Häder, Donat-Peter (Protoplasma, 2006)
The effects of the calcium sequester EGTA on gravitactic orientation and membrane potential changes in the unicellular flagellate Euglena gracilis were investigated during a recent parabolic-flight experiment aboard of an Airbus A300. In the Course of a flight parabola, an acceleration profile is achieved which yields Subsequently about 20 s of hypergravity (1.8 g(n)), about 20 s of microgravity, and another 20 s of hypergravity phases. The movement behavior of the cells was investigated with real-time, computer-based image analysis. Membrane potential changes were detected with a newly developed photometer which measures absorption changes of the membrane potential-sensitive probe oxonol VI. To test whether the data obtained by the oxonol device were reliable, the signal of non-oxonol-labelled cells was recorded. In these samples, no absorption shift was detected. Changes of the oxonol VI signals indicate that the cells depolarize during acceleration (very obvious in the step from microgravity to hypergravity) and slightly hyperpolarize in microgravity. which can possibly be explained with the action of Ca-ATPases. These signals (mainly the depolarization) were significantly suppressed in the presence of EGTA (5 mM). Gravitaxis in parallel was also inhibited after addition of EGTA. Initially. negative gravitaxis was inverted into a positive one. Later, gravitaxis was almost undetectable.
Keywords: Euglena gracilis; gravitaxis; image analysis; EGTA; oxonol VI; parabolic-flight campaign

Influence of Different Light-Dark Cycles on Motility and Photosynthesis of Euglena gracilis in Closed Bioreactors - Richter, Peter; Strauch, Sebastian; Ntefidou, Maria; Schuster, Martin; Daiker, Viktor; Nasir, Adeel; Haag, Ferdinand; Lebert, Michael (Astrobiology, 2014)
The unicellular photosynthetic freshwater flagellate Euglena gracilis is a promising candidate as an oxygen producer in biological life-support systems. In this study, the capacity of Euglena gracilis to cope with different light regimes was determined. Cultures of Euglena gracilis in closed bioreactors were exposed to different dark-light cycles (40 W/m(2) light intensity on the surface of the 20 L reactor; cool white fluorescent lamps in combination with a 100 W filament bulb): 1 h-1 h, 2 h-2 h, 4 h-4 h, 6 h-6 h, and 8 h-16 h, respectively. Motility and oxygen development in the reactors were measured constantly. It was found that, during exposure to light-dark cycles of 1 h-1 h, 2 h-2 h, 4 h-4 h, and 6 h-6 h, precision of gravitaxis as well as the number of motile cells increased during the dark phase, while velocity increased in the light phase. Oxygen concentration did not yet reach a plateau phase. During dark-light cycles of 8 h-16 h, fast changes of movement behavior in the cells were detected. The cells showed an initial decrease of graviorientation after onset of light and an increase after the start of the dark period. In the course of the light phase, graviorientation increased, while motility and velocity decreased after some hours of illumination. In all light profiles, Euglena gracilis was able to produce sufficient oxygen in the light phase to maintain the oxygen concentration above zero in the subsequent dark phase. Key Words: Euglena gracilis-Bioreactor-Light-dark cycle-Motility-Gravitaxis. Astrobiology 14, 848-858.

Influence of microgravity on apoptosis in cells, tissues, and other systems in vivo and in vitro - Prasad, Binod; Grimm, Daniela; Strauch, Sebastian M.; Erzinger, Gilmar Sidnei; Corydon, Thomas J.; Lebert, Michael; Magnusson, Nils E.; Infanger, Manfred; Richter, Peter; Krüger, Marcus (International Journal of Molecular Sciences, 2020)
All life forms have evolved under the constant force of gravity on Earth and developed ways to counterbalance acceleration load. In space, shear forces, buoyance-driven convection, and hydrostatic pressure are nullified or strongly reduced. When subjected to microgravity in space, the equilibrium between cell architecture and the external force is disturbed, resulting in changes at the cellular and sub-cellular levels (e.g., cytoskeleton, signal transduction, membrane permeability, etc.). Cosmic radiation also poses great health risks to astronauts because it has high linear energy transfer values that evoke complex DNA and other cellular damage. Space environmental conditions have been shown to influence apoptosis in various cell types. Apoptosis has important functions in morphogenesis, organ development, and wound healing. This review provides an overview of microgravity research platforms and apoptosis. The sections summarize the current knowledge of the impact of microgravity and cosmic radiation on cells with respect to apoptosis. Apoptosis-related microgravity experiments conducted with different mammalian model systems are presented. Recent findings in cells of the immune system, cardiovascular system, brain, eyes, cartilage, bone, gastrointestinal tract, liver, and pancreas, as well as cancer cells investigated under real and simulated microgravity conditions, are discussed. This comprehensive review indicates the potential of the space environment in biomedical research.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Apoptosis; Astronauts; Cells; Cosmic radiation; Mice; Microgravity; Rats; Spaceflight; Tissues

Investigation of Gravitaxis and Phototaxis in Euglena gracilis - Häder, Donat-Peter; Faddoul, Jaoudat; Lebert, Michael; Richter, Peter; Schuster, Martin; Richter, Roland; Strauch, Sebastian; Daiker, Viktor (Advances in Life Sciences, 2010)
This article provides an overview of the research of phototaxis and gravitaxis in the unicellular flagellate Euglena gracilis. The cells show positive phototaxis at low light intensities (swimming towards the light source, below 10 W/m2, sunlight) and a negative one upon high irradiances (>10 W/m2). Phototaxis is based on a blue light-activated adenylyl cyclase, which produces cAMP upon irradiation. The further steps following the transient rise of the cAMP concentration are still unknown. Gravitaxis is a movement parallel to an acceleration vector. In the absence of external stimuli the cells swim upward in the water column (negative gravitaxis), upon stress gravitaxis inverts into a positive one. The results of sounding rocket campaigns and of a large number of ground experiments led to the following model of signal perception and transduction in gravitaxis of Euglena gracilis: The body of the cell is heavier than the surrounding medium, sediments and thereby exerts a force onto the lower membrane. Upon deviation from a vertical swimming path mechano-sensitive elements are activated. This leads to an increase in the intracellular calcium concentration and a change of the membrane potential. The increased calcium concentration regulates the action of calmodulin, which in turn modulates an adenylyl cyclase, which converts ATP to cAMP. cAMP probably controls the flagellar beat and/or probably the shape of the cell. Phototaxis as well as gravitaxis are probably controlled by certain protein kinases. The blockage of different protein kinases (PK) by means of RNAi gave rise to the assumption that both signal pathways activate certain PKs. The blockage of one PK resulted in a loss of gravitaxis, the blockage of another one in loss of phototactic behaviour.
Keywords: Euglena gracilis; phototaxis; gravitaxis; RNA interference; signal transduction

Investigation of gravity-related swimming behavior of unicellular flagellates - Richter, Peter; Häder, Donat-Peter; Lebert, Michael; Schuster, Martin; Daiker, Viktor; Strauch, Sebastian (Proceedings of the 18th ESA Symposium on European Rocket and Balloon Programmes and Related Research, 2007)
Sounding rockets are valuable experimental platforms for investigation of gravity-related physiological mechanism in living organisms. The obtained microgravity quality is excellent and the time scale of 6 -14 min microgravity is sufficient to examine various physiological parameters. Freefall or space experiments are the only possibility to avoid gravity and to obtain mechano-sensitive structures in a non-influenced state. Our group uses sounding rocket experiments to investigate the gravity-oriented movement behavior of the unicellular flagellate Euglena gracilis. In intensive laboratory experiments and during the course of eight TEXUS and two MAXUS campaigns it was found that the movement of the cells with respect to the gravity vector is controlled by an active physiological mechanism. The. experiments indicated possible elements of a signal transduction chain, which is presently under investigation by means of molecular biological methods.

Latest knowledge about changes in the proteome in microgravity - Schulz, Herbert; Strauch, Sebastian M.; Richter, Peter; Wehland, Markus; Krueger, Marcus; Sahana, Jayashree; Corydon, Thomas J.; Wise, Petra; Baran, Ronni; Lebert, Michael; Grimm, Daniela (Expert Review of Proteomics, 2022)
Introduction A long-term stay of humans in space causes health problems and changes in protists and plants. Deep space exploration will increase the time humans or rodents will spend in microgravity (mu g). Moreover, they are exposed to cosmic radiation, hypodynamia, and isolation. OMICS investigations will increase our knowledge of the underlying mechanisms of mu g-induced alterations in vivo and in vitro. Areas covered We summarize the findings over the recent 3 years on mu g-induced changes in the proteome of protists, plants, rodent, and human cells. Considering the thematic orientation of microgravity-related publications in that time frame, we focus on medicine-associated findings, such as the mu g-induced antibiotic resistance of bacteria, the myocardial consequences of mu g-induced calpain activation, and the role of MMP13 in osteoarthritis. All these point to the fact that mu g is an extreme stressor that could not be evolutionarily addressed on Earth. Expert opinion In conclusion, when interpreting mu g-experiments, the direct, mostly unspecific stress response, must be distinguished from specific mu g-effects. For this reason, recent studies often do not consider single protein findings but place them in the context of protein-protein interactions. This enables an estimation of functional relationships, especially if these are supported by epigenetic and transcriptional data (multi-omics).
CRIS-Team WoS Importer:2022-02-11

Molecular analysis of the graviperception signal transduction in the flagellate Euglena gracilis: Involvement of a transient receptor potential-like channel and a calmodulin - Häder, Donat-Peter; Richter, Peter; Schuster, Martin; Daiker, Viktor; Lebert, Michael (Advances in Space Research, 2009)
Euglena gracilis, a unicellular, photosynthetic flagellate is a model system for environmentally controlled behavior responses. The organism shows pronounced negative gravitaxis. This movement is based oil physiological mechanisms, which in the past had been only indirectly assessed. It was shown that mechano-sensitive calcium channels are involved in the gravitaxis response. Recent studies have demonstrated that members of the transient receptor potential (TRP) family function as mechano-sensitive channels in several different cell types. We have sequenced part of a TRP gene in Euglena and applied RNA interference (RNAi) to confirm that these channels are involved in graviperception. It was found that RNAi against the putative TRP channel abolished gravitaxis. The genes of three calmodulins were sequences in Euglena, one of which was previously known in its protein structure (cal 1). The other two were unknown (cal 2 and call 3). Cal 2 has been analyzed in detail. The biosynthesis of the corresponding proteins of cal I and cal 2 was inhibited by means of RNA interference to see whether this blockage impairs gravitaxis. RNAi of cal I leads to a long-term loss of free swimming in the cells (while euglenoid movement persists). It induced pronounced cell form aberrations and the division of cells was hampered. After recovery from RNAi the cell showed precise negative gravitaxis again. Thus cal I does not seem to be involved in gravitaxis. In contrast, the blockage of cal 2 has no pronounced influence oil motility and cell form but leads to a complete loss of gravitactic orientation for more than 30 days showing that this calmodulin is an element in the signal transduction chain. The data are discussed in the context of the current model of the gravitaxis signal transduction chain in Euglena gracilis. (C) 2009 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Euglena gracilis; Gravitaxis; Signal transduction; Mechano-sensitive channel; Calmodulin

Molecular characterization of a calmodulin involved in the signal transduction chain of gravitaxis in Euglena gracilis - Daiker, Viktor; Lebert, Michael; Richter, Peter; Häder, Donat-Peter (Planta, 2010)
The unicellular flagellate Euglena gracilis shows a negative gravitactic behavior. This is based on physiological mechanisms which in the past have been indirectly assessed. Meanwhile, it was possible to isolate genes involved in the signal transduction chain of gravitaxis. The DNA sequences of five calmodulins were found in Euglena, one of which was only known in its protein structure (CaM.1); the other four are new. The biosynthesis of the corresponding proteins of CaM.1-CaM.5 was inhibited by means of RNA interference to determine their involvement in the gravitactic signal transduction chain. RNAi of CaM.1 inhibits free swimming of the cells and pronounced cell-form aberrations. The division of cells was also hampered. After recovery from RNAi the cell showed precise negative gravitaxis again. Blockage of CaM.3 to CaM. 5 did not impair gravitaxis. In contrast, the blockage of CaM.2 has only a transient and not pronounced influence on motility and cell form, but leads to a total loss of gravitactic orientation for more than 30 days. This indicates that CaM.2 is an element in the signal transduction chain of gravitaxis in E. gracilis. The results are discussed with regard to the current working model of gravitaxis in E. gracilis.
Keywords: Calmodulin; Euglena; Gravitaxis; RNA interference

Molecular Cross-Talk between Gravity-and Light-Sensing Mechanisms in Euglena gracilis - Nasir, Adeel; Richter, Peter; le Bail, Aude; Daiker, Viktor; Stoltze, Julia; Prasad, Binod; Strauch, Sebastian Michael; Lebert, Michael (International Journal of Molecular Sciences, 2022)
Euglena gracilis is a photosynthetic flagellate. To acquire a suitable position in its surrounding aquatic environment, it exploits light and gravity primarily as environmental cues. Several physiological studies have indicated a fine-tuned relationship between gravity sensing (gravitaxis) and light sensing in E. gracilis. However, the underlying molecular mechanism is largely unknown. The photoreceptor photoactivated adenylyl cyclase (PAC) has been studied for over a decade. Never-theless, no direct/indirect interaction partner (upstream/downstream) has been reported for PAC. It has been shown that a specific protein, kinase A (PKA), showed to be involved in phototaxis and gravitaxis. The current study reports the localization of the specific PKA and its relationship with PAC.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Euglena gracilis; Gravitaxis; Indirect immuno-fluorescent assay; Movement analysis; Photoactivated adenylyl cyclase; Phototaxis; Protein kinase A; RNA interference

Natural products in modern biology: Ancient wisdom for today’s challenges - Krüger, Marcus; Richter, Peter; Strauch, Sebastian M. (Biology, 2021)
CRIS-Team Scopus Importer:2021-05-21

Operation of an enclosed aquatic ecosystem in the Shenzhou-8 mission - Li, Xiaoyan; Richter, Peter; Hao, Zongjie; An, Yanjun; Wang, Gaohong; Li, Dunhai; Liu, Yongding; Strauch, Sebastian; Schuster, Martin; Haag, Ferdinand; Lebert, Michael (Acta Astronautica, 2017)
Long- term spaceflight needs reliable Biological life support systems (BLSS) to supply astronauts with enough food, fresh air and recycle wasters, but the knowledge about the operation pattern and controlling strategy is rear. For this purpose, a miniaturized enclosed aquatic ecosystem was developed and flown on the Chinese spaceship Shenzhou-8. The system with a total volume of about 60 mL was separated into two chambers by means of a gas transparent membrane. The lower chamber was inoculated with Euglena gracilis cells, and the upper chamber was cultured with Chlorella cells and three snails. After 17.5 days flight, the samples were analyzed. It was found that all snails in the ground module (GM) were alive, while in the flight module (FM) only one snail survived. The total cell numbers, assimilation of nutrients like nitrogen and phosphorus, soluble proteins and carbohydrate contents showed a decrease in FM than in GM. The correlation analysis showed upper chambers of both FM and GM had the same positive and negative correlation factors, while differential correlation was found in lower chambers. These results suggested primary productivity in the enclosed system decreased in microgravity, accompanied with nutrients assimilation. The FM chamber endured lacking of domination species to sustain the system development and GM chamber endured richness in population abundance. These results implied photosynthesis intensity should be reduced to keep the system healthy. More Chlorella but less Euglena might be a useful strategy to sustain system stability. It is the first systematic analysis of enclosed systems in microgravity.
Keywords: Chlorella pyrenoidosa; enclosed aquatic ecosystem; Euglena gracilis; life support system; microgravity; Shenzhou-8

Optimizing conditions for the use of chlorophyll derivatives for photodynamic control of parasites in aquatic ecosystems - Erzinger, Gilmar Sidnei; Wohllebe, Stephanie; Vollrath, Fernanda; Souza, Suellen Carolina; Richter, Peter; Lebert, Michael; Häder, Donat-Peter (Parasitology Research, 2011)
Recently, it was demonstrated that mosquito larvae can be killed by means of photodynamic processes after the larvae have incorporated the photosensitizer chlorophyllin or pheophorbid, and were treated with light. The water-soluble substances were applied to and incorporated by the larvae in darkness. With Chaoborus sp. a dark incubation of about 3 h is sufficient to yield mortality of about 90% and a parts per thousand yen6 h resulted in almost 100% mortality during subsequent illumination. Temperature did not influence mortality of the larvae significantly in a treatment of 6 h dark incubation and subsequent 3 h illumination. At 10A degrees C, 20A degrees C, or 30A degrees C, between 80% and 100% of the treated larvae died when the light intensity from a solar simulator was above 30 W/m(2). Lower irradiances were less effective. The LD(50) value of magnesium chlorophyllin was about 22.25 mg/l and for Zn chlorophyll 17.53 mg/l, while Cu chlorophyll (LD(50) 0.1 mg/l) was shown to be toxic also without light. Chlorophyllin, which was lyophilized immediately after extraction, was far more lethal to the larvae (LD(50) 14.88 mg/l) than air-dried Mg chlorophyllin.

Photodynamic Activity of Chlorophyllin and Polyethylenimine on Pseudomonas aeruginosa Planktonic, Biofilm and Persister Cells - Mahmoud, Mona; Richter, Peter; Lebert, Michael; Burkovski, Andreas (International Journal of Molecular Sciences, 2023)
Antimicrobial photodynamic inactivation is considered a promising antimicrobial approach that may not develop resistance in the near future. Here, we investigate the influence of the photosensitizer chlorophyllin (CHL) and the cationic permeabilizer polyethylenimine (PEI), exposed to a red light-emitting diode, on the human pathogen Pseudomonas aeruginosa free-living planktonic cells, the sessile biofilm and persister cells. The broth microdilution checkerboard method was used to test antimicrobial susceptibility. As a substrate for biofilms, the Calgary biofilm device was used, and the quantification of the biofilm biomass was carried out using a crystal violet assay. Serine hydroxamate was used for the induction of persisters. Our findings reveal that PEI ameliorates the antimicrobial activity of CHL against P. aeruginosa planktonic and biofilm states, and the concentration required to eradicate the bacteria in the biofilm is more than fourfold that is required to eradicate planktonic cells. Interestingly, the persister cells are more susceptible to CHL/PEI (31.25/100 µg mL−1) than the growing cells by 1.7 ± 0.12 and 0.4 ± 0.1 log10 reduction, respectively, after 15 min of illumination. These data demonstrate that CHL excited with red light together with PEI is promising for the eradication of P. aeruginosa, and the susceptibility of P. aeruginosa to CHL/PEI is influenced by the concentrations and the exposure time.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antimicrobial resistance; dormant bacteria; photosensitizer; stringent response

Photodynamic Treatment of Chaoborus crystallinus Larvae with Chlorophyllin Induces Necrosis and Apoptosis - Wohllebe, Stephanie; Ulbrich, Claudia; Grimm, Daniela; Pietsch, Jessica; Erzinger, Gilmar; Richter, Roland; Lebert, Michael; Richter, Peter; Haeder, Donat-Peter (Photochemistry and Photobiology, 2011)
Chlorophyllin kills mosquito larvae (Culex, Aedes) in the aquatic habitat at low concentrations via photodynamic reactions under irradiation. The effects of chlorophyllin were investigated at the cellular level using the transparent larvae of Chaoborus crystallinus as a model system. Their transparency enabled in situ fluorescence investigation, showing that chlorophyllin accumulates in the intestine of the larvae. Uptake of chlorophyllin at room temperature took about 2 h. The fluorescence signal peaked after 5 h of incubation. Chlorophyllin accumulates up to about 15 ng per larvae. The intestine of treated larvae was dissected and stained with several dyes (acridine orange, Hoechst 33342 and propidium iodide). Apoptosis and necrosis increased with higher concentrations of chlorophyllin (to a smaller extent in dark controls) and were elevated in irradiated samples. Single cells from treated larvae were isolated and subjected to Annexin V flow cytometry. The fraction of apoptotic and necrotic cells increased significantly at a high chlorophyllin concentration (21.4 mg L(-1)) and under intensive irradiation. The activity of caspases-3, -8 and -9 as well as Bcl-2 and cytochrome c was investigated by means of western blot analysis. The data suggest a possible chlorophyllin concentration-dependent shift of the apoptotic pathway.

Physiological characterization of gravitaxis in Euglena gracilis and Astasia longa studied on sounding rocket flights. - Richter, Peter; Lebert, Michael; Tahedl, Harald; Häder, Donat-Peter (Advances in Space Research, 2001)
Euglena gracilis is a photosynthetic, unicellular flagellate found in eutrophic freshwater habitats. The organisms control their vertical position in the water column using gravi- and phototaxis. Recent experiments demonstrated that negative gravitaxis cannot be explained by passive buoyancy but by an active physiological mechanism. During space experiments, the threshold of gravitaxis was determined to be between 0.08 and 0.12 × g. A strong correlation between the applied acceleration and the intracellular cAMP and Ca2+ was observed. The results support the hypothesis, that the cell body of Euglena, which is denser than the surrounding medium exerts a pressure onto the lower membrane and activates mechano-sensitive Ca2+ channels. Changes in the membrane potential and the cAMP concentration are most likely subsequent elements in a signal transduction chain, which results in reorientation strokes of the flagellum. © 2001 COSPAR. Published by Elsevier Science Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2001.nat.dbio.LBIPDH.physio

Physiological parameters of gravitaxis in the flagellate Euglena gracilis obtained during a parabolic flight campaign - Richter, Peter; Schuster, Martin; Wagner, Helmut; Lebert, Michael; Häder, Donat-Peter (Journal of Plant Physiology, 2002)
The unicellular freshwater flagellate Euglena gracilis and its close relative Astasia longa show a pronounced negative gravitaxis. Previous experiments revealed that gravitaxis is most likely mediated by an active physiological mechanism in which changes of the internal calcium concentration and the membrane potential play an important role. In a recent parabolic flight experiment on board an aircraft (ESA 29th parabolic flight campaign), changes of graviorientation, membrane potential and the cytosolic calcium concentration upon changes of the acceleration (between 1 x g(n), 1.8 x g(n), microgravity) were monitored by image analysis and photometric methods using Oxonol VI (membrane potential) and Calcium Crimson (cytosolic calcium concentration). The parabolic flight maneuvers performed by the aircraft resulted in transient phases of 1.8 x g(n) (about 20s), microgravity (about 22s) followed by 1.8 x g(n) (about 20s). A transient increase in the intracellular calcium concentration was detected from lower to higher accelerations (1 x g(n) to 1.8 x g(n) or microgravity to 1.8 x g(n)). Oxonol VI-labeled cells showed a signal, which indicates a depolarization during the transition from 1 x g(n) to 1.8 x g(n), a weak repolarization in microgravity followed by a rapid repolarization in the subsequent 1 x g(n) phase. The results show good coincidence with observations of recent terrestrial and space experiments.
Keywords: Astasia longa; calcium; Calcium Crimson; dynamic calcium imaging; Euglena gracilis; gravitaxis; membrane potential; Oxonol VI; signal transduction

Polyethylenimine Increases Antibacterial Efficiency of Chlorophyllin - Akif, Faheem Ahmad; Mahmoud, Mona; Prasad, Binod; Richter, Peter; Azizullah, Azizullah; Qasim, Muhammad; Anees, Muhammad; Krueger, Marcus; Gastiger, Susanne; Burkovski, Andreas; Strauch, Sebastian M.; Lebert, Michael (Antibiotics, 2022)
Polyethylenimines (PEIs), a group of polycationic molecules, are known to impair the outer membrane of Gram-negative bacteria and exhibit antimicrobial activity. The outer membrane of Gram-negative strains hinders the uptake of photosensitizer chlorophyllin. In this study, we report chlorophyllin and branched PEI combinations’ activity against Escherichia coli strains DH5α and RB791, Salmonella enterica sv. Typhimurium LT2, and Bacillus subtilis 168. The minimal bactericidal concentration (MBC) was determined by plating cells treated with different concentrations of PEI and chlorophyllin on agar and monitoring their growth after 24 h. All tested combinations of PEI and chlorophyllin were lethal for S. enterica after 240 min of incubation in light, whereas PEI alone (<100 µg mL−1) was ineffective. In the darkness, complete inhibition was noted with a combination of ≥2.5 µg mL−1 chlorophyllin and 50 µg mL−1 PEI. If applied alone, PEI alone of ≥800 µg mL−1 of PEI was required to completely inactivate E. coli DH5α cells in light, whereas with ≥5 µg mL−1 chlorophyllin, only ≥100 µg mL−1 PEI was needed. No effect was detected in darkness with PEI alone. However, 1600 µg mL−1 PEI in combination with 2.5 µg mL−1 resulted in complete inactivation after 4 h dark incubation. PEI alone did not inhibit E. coli strain RB791, while cells were inactivated when treated with 10 µg mL−1 chlorophyllin in combination with ≥100 µg mL−1 (in light) or ≥800 µg mL−1 PEI (in darkness). Under illumination, B. subtilis was inactivated at all tested concentrations. In the darkness, 1 µg mL−1 chlorophyllin and 12.5 µg mL−1 PEI were lethal for B. subtilis. Overall, PEI can be used as an antimicrobial agent or potentiating agent for ameliorating the antimicrobial activity of chlorophyllin.
CRIS-Team Scopus Importer:2022-11-04
Keywords: chlorophyllin; photodynamic antimicrobial activity; polyethlyenimine; synergistic effect

Possible involvement of the membrane potential in the gravitactic orientation of Euglena gracilis - Richter, Peter; Lebert, Michael; Korn, René; Häder, Donat-Peter (Journal of Plant Physiology, 2001)
Euglena gracilis, a unicellular photosynthetic flagellate, uses light and gravity as environmental hints to reach and stay in regions optimal for growth and reproduction. The current model of gravitaxis (the orientation with respect to the earth's gravitational field) is based on the specific density difference between cell body and medium. The resulting sedimentation of the cell body applies a force to the lower membrane. This force activates mechano-sensitive ion channels. The resulting ion flux changes the membrane potential, which in turn triggers reorientational movements of the trailing flagellum. One possibility for recording the predicted membrane potential changes during reorientation is the use of potential-sensitive dyes, such as Oxonol VI. The absorption changes of the dye indicating potential changes were recorded with a custom-made photometer, which allows a high precision measurement with a high temporal resolution. After a gravitactic stimulation, a short period of hyperpolarization was detected, followed by a massive depolarization of the cell. The membrane potential returned to initial values after a period of approximately 200s. Parallel measurements of the precision of orientation and the membrane potential showed a close relationship between both phenomena. The obtained results support the current model of gravitaxis of Euglena gracilis.
UnivIS-Import:2015-03-09:Pub.2001.nat.dbio.LBIPDH.possib
Keywords: Euglena gracilis; Gravitaxis; Membrane potential; Oxonol VI; Signal transduction

R3D-B2 Measurement of ionizing and solar radiation in open space in the BIOPAN 5 facility outside the FOTON M2 satellite - Häder, Donat-Peter; Richter, Peter; Schuster, Martin; Dachev, Ts.; Tomov, B.; Georgiev, Pl.; Matviichuk, Yu. (Advances in Space Research, 2009)
Solar and space radiation have been monitored using the R3D-B2 radiation risks radiometer-dosimeter oil board a recent space flight oil the Russian satellite Foton M2 within the ESA Biopan 5 facility mounted oil the outside of the satellite exposed to space conditions. The solar radiation has been assayed in four wavelength bands (UV-C, 170-280 nm, UV-B, 280-315 nm), UV-A (315-400 nm) and PAR (photosynthetic active radiation, 400-700 rim). The data show ail increasing tumbling rotation of the satellite during the mission. The photodiodes do not show a cosine response to the incident light which has been corrected. After calibration of the signals using the extraterrestrial spectrum, doses have been calculated for each orbit, for each day and for the total mission as basic data for the biological material which has been exposed in parallel in the Biopan facility. Cosmic ionizing radiation has been monitored and separated in 256 deposited energy spectra, which were further used for determination of the absorbed dose rate and flux. Basic data tables were prepared to be used by other Biopan 5 experiments. The paper summarizes the results for the Earth radiation environment at the altitude (262-304 km) of the Foton M2 spacecraft. Comparisons with the predictions of NASA Earth radiation environment experimental models AE-8 and AP-8, and the PSB97 model are also presented, which calculate the fluxes of ionizing radiation from a simulation. AP-8 is a model for trapped radiation. (C) 2009 COSPAR. Published by Elsevier Ltd. All rights reserved.
Keywords: Biopan facility; Cosmic ionizing radiation; Extraterrestrial radiation; Foton satellite; Solar radiation; UV radiation

R3D-B, radiation risk radiometer-dosimeter on BIOPAN (Foton) and EXPOSE on the International Space Station (ISS) - Streb, Christine; Richter, Peter; Lebert, Michael; Dachev, Tsvetan; Häder, Donat-Peter (PROCEEDINGS OF THE SECOND EUROPEAN WORKSHOP ON EXO-ASTROBIOLOGY, 2002)
The radiation risk radiometer-dosimeter R3D is designed to measure the radiation climate during the long-term life science experiment SPORES on the ISS. In October 2002 the device will be tested under space conditions on the Biopan facility of the Foton satellite. During the whole BIOPAN-4 campaign the solar and ionizing conditions will be monitored by this newly developed measurement device. The R3D is based on two existing prototypes: first the ELDONET system (developed for the European light dosimeter network) used for terrestrial monitoring of solar radiation (UV-A, UV-B and photosynthetically active radiation) and second the measurement of ionizing radiation in space by the Liulin instrument on the MIR space station.

R3DE: Radiation Risk Radiometer-Dosimeter on the International Space Station-Optical Radiation Data Recorded During 18 Months of EXPOSE-E Exposure to Open Space - Schuster, Martin; Dachev, Tsvetan; Richter, Peter; Haeder, Donat-Peter (Astrobiology, 2012)
Radiation Risk Radiometer-Dosimeter E (R3DE) served as a device for measuring ionizing and non-ionizing radiation as well as cosmic radiation reaching biological samples located on the EXPOSE platform EXPOSE-E. The duration of the mission was almost 1.5 years (2008-2009). With four channels, R3DE detected the wavelength ranges of photosynthetically active radiation (PAR, 400-700 nm), UVA (315-400 nm), UVB (280-315 nm), and UVC (<280 nm). In addition, the temperature was recorded. Cosmic ionizing radiation was assessed with a 256-channel spectrometer dosimeter (see separate report in this issue). The light and UV sensors of the device were calibrated with spectral measurement data obtained by the Solar Radiation and Climate Experiment (SORCE) satellite as standard. The data were corrected with respect to the cosine error of the diodes. Measurement frequency was 0.1 Hz. Due to errors in data transmission or temporary termination of EXPOSE power, not all data could be acquired. Radiation was not constant during the mission. At regular intervals of about 2 months, low or almost no radiation was encountered. The radiation dose during the mission was 1823.98 MJ m(-2) for PAR, 269.03 MJ m(-2) for UVA, 45.73 MJ m(-2) for UVB, or 18.28 MJ m(-2) for UVC. Registered sunshine duration during the mission was about 152 days (about 27% of mission time). The surface of EXPOSE was most likely turned away from the Sun for considerably longer. R3DE played a crucial role on EXPOSE-EuTEF (EuTEF, European Technology Exposure Facility), because evaluation of the astrobiology experiments depended on reliability of the data collected by the device. Observed effects in the samples were weighted by radiation doses measured by R3DE.
Keywords: EXPOSE-E; R3DE; Radiation measurement; PAR; UV radiation

Red-emitting Ca 1-xSr xS:Eu 2+ phosphors as light converters for plant-growth applications - Xia, Qi; Batentschuk, Miroslaw; Osvet, Andres; Richter, Peter; Häder, Donat-Peter; Schneider, Jürgen; Wondraczek, Lothar; Winnacker, Albrecht; Brabec, Christoph (2011 MRS Spring Meeting, 2012)
A series of Ca Sr S:Eu phosphors were synthesized with solid state reactions and with various Ca/Sr ratio and Eu doping concentrations. The influences of the lattice composition and the Eu doping level on photoluminescent properties were analyzed. With doping concentrations between 0.1 to 3 mol%, concentration quenching takes place leading to the decrease of luminance; the emission maxima are also red-shifted. Further, this work reports enhanced photosynthetic activities of intact spinach leaves due to spectral modification of simulated solar irradiation by one synthesized phosphor (Ca Sr S:Eu ). The CO assimilation rates of intact spinach leaves were monitored with an effective homemade photosynthesis measurement system with controlled light conditions. The phosphor could efficiently convert the photosynthetically less active green part of the solar spectrum into the red, with a broad-band red emission centered at 650 nm and a halfband-width of 68 nm, giving an excellent match with the absorption spectrum of spinach chloroplasts. By careful referencing the photon flux, we found an enhanced photosynthetic activities by about 30% due to the emission of the phosphor. © 2011 Materials Research Society.
Keywords: Assimilation rate; Broad bands; Concentration quenching; Doping concentration; Doping levels; Emission maxima; Light conditions; Measurement system; Photo-luminescent properties; Photon flux; Photosynthetic activity; Red emissions; Red-shifted; Solar irradiation; Solar spectrum; Spectral modifications; Spinach leaves Engineering controlled terms: Calcium; Carbon dioxide; Light emission; Phosphors; Solar radiation; Solid state reactions Engineering main heading: Europium

Restart capability of resting-states of Euglena gracilis after 9 months of dormancy: preparation for autonomous space flight experiments - Strauch, Sebastian; Becker, Ina; Pölloth, Laura; Richter, Peter; Haag, Ferdinand; Hauslage, Jens; Lebert, Michael (International Journal of Astrobiology, 2017)
Dormant states of organisms are easier to store than the living statebecause they tolerate larger variations in  temperature, light, storage space etc., making them attractive for lab culture stocks and also for experiments under special circumstances, especially space flight experiments. Like several other organisms, Euglena gracilis is capable of forming desiccation tolerant resting states in order to survive periods of  unfavorable environmental conditions. In earlier experiments it was found that dormant Euglena cells must not become completely desiccateed. Some residual moisture is required to ensure recovery of the resting states. To analyze the water demand in recovery of Euglena resting states, cells were transferred to a defined amount of cotton wool (0.5 g). Subsequently different volumes of medium (1, 2, 3, 4, 5, 8, 10, and 20 mL) were added in order to supply humidity; a control was set up without additional liquid. Samples were sealed in transparent 50 mL falcon tubes and stored for 9 months under three different conditions: Constant low light conditions in a culture chamber at 20° C, In a black box, illuminated with short LED-light pulses provided by joule thieves, and In darkness in a black box. After nine months, cells were transferred to fresh medium and cell number, photosynthetic efficiency, and movement behavior was monitored over 3 weeks. It was found that cells recovered under all conditions except in the control, where no medium was supplied. Transcription levels of 21 genes were analyzed with a Multiplex-PCR. One hour after rehydration 5 of these genes were found to be up-regulated: ubiquitin, HSP70, HSP90, the calcium-sensor protein frequenin and a distinct protein kinase (PKA), which is involved in gravitaxis. The results indicate a transient general stress response of the cells.
Keywords: dormancy; resting states; Euglena gracilis; recovery; HSP70; HSP90; Multiplex-PCR; ubiquitin; frequenin; PKA

Sensory transduction of gravitaxis in Euglena gracilis - Streb, Christine; Richter, Peter; Ntefidou, Maria; Lebert, Michael; Häder, Donat-Peter (Journal of Plant Physiology, 2002)
Euglena gracilis is a single-celled freshwater flagellate which shows, among other movement behaviors, a negative gravitaxis (cells swim upward in the water column) and a pronounced phototaxis. Gravitaxis is most likely an active physiological mechanism, and the influence of various inhibitors on the gravitaxis in Euglena gracilis was tested using the fully automatic image analysis system ECO-TOX to elucidate the possible cellular mechanism of gravity perception and signal transduction. Substances such as the phosphodiesterase inhibitors theophylline, IBM-X and forskolin, which increase the intracellular cAMP concentration, enhance the precision of graviorientation of the cells measured shortly after incubation. Indomethacin, which decreases the intracellular cAMP concentration by inhibition of the adenylate cyclase, inhibited graviorientation. All inhibitors of calmodulin metabolism tested reduced the precision of gravitaxis in Euglena gracilis. Heparin and LiCl, which inhibit the IP3-pathway (block IP3 channels or formation of IP3, respectively) had no effect. The potassium channel blockers BaCl2 and CsCl showed an effect on the orientation behavior, while tetraethylammonium (TEA) had no influence. The protein phosphatase inhibitor, ocadaic acid, inhibited graviorientation at low concentrations. The data are discussed with respect to the current working model for gravitaxis in Euglena gracilis.
Keywords: calmodulin; cyclic nucleotides; Euglena gracilis; flagellates; gravitaxis; sensory transduction

Spaceflight Microgravity Reduced Photosynthetical Electron Transport and Altered Energy Distribution in Euglena gracilis - Li, Xiaoyan; Li, Gen-Bao; Li, Dun-Hai; Hao, Zong-Jie; Wang, Gaohong; Richter, Peter; Schuster, Martin; Lebert, Michael; Liu, Yongding (Progress in Biochemistry and Biophysics, 2016)
The effects of 17-day spaceflight microgravity on the photosynthetic activity of Euglena gracilis were investigated during the SIMBOX mission on board the Chinese Shenzhou-8 spacecraft. We found that microgravity decreased Fv/Fm, while chlorophyll a and carotenoid contents were increased. The fluorescence yields were clearly reduced by microgravity, but the shape of fluorescence transients (O-J-I-P) was not changed. The quantum yield of primary photochemistry (cpPo), the quantum yield of electron transport (cpEo) and the performance index of PS II (PIABS and PICS) in microgravity group were decreased, while ABS/RC and DIo/RC were increased. 77K fluorescence emission spectra indicated that microgravity altered energy distribution between PS II and PS I and there are redshifts under microgravity. These results suggested that microgravity may impair photosynthesis by inhibition of acceptor sides of PS II in electron transfer pathway and alter PS I structure to cause a reduction of energy transfer to PS I in Euglena gracilis.
Keywords: microgravity; photosynthesis; chlorophyll a fluorescence; Euglena gracilis; electron transport

The beating pattern of the flagellum of Euglena gracilis under altered gravity during parabolic flights - Strauch, Sebastian; Richter, Peter; Schuster, Martin; Häder, Donat-Peter (Journal of Plant Physiology, 2010)
The unicellular freshwater flagellate Euglena gracilis shows negative gravitactic behavior. Previous experiments have revealed that the orientation is most likely an active physiological process in which the beating pattern of the flagellum is controlled by gravity and mediated by a change in the calcium concentration inside the cell. In a signal transduction chain, the calcium signal activates a calmodulin, which in turn raises the concentration of cAMR This alters the beating pattern of the flagellum; reorientation is therefore not a passive process driven by buoyancy. In a recent parabolic flight experiment (ESA 45th parabolic flight campaign), we observed the beating of the flagellum with a high-resolution light microscope. Transition from hyper g to mu g as well as from mu g to hyper g caused a change of the beating pattern of the flagellum, which confirmed the physiological nature of the process. In mu g cells stopped moving the flagellum or tried to reorient, while in hyper g, the cells realigned consecutively. The reaction times for the flagellar responses in previous experiments are confirmed. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: Euglena gracilis; Flagellum; Gravitaxis; Microscopy; Weightlessness

The effects of microgravity on differentiation and cell growth in stem cells and cancer stem cells - Grimm, Daniela; Wehland, Markus; Corydon, Thomas J.; Richter, Peter; Prasad, Binod; Bauer, Johann; Egli, Marcel; Kopp, Sascha; Lebert, Michael; Krüger, Marcus (Stem Cells Translational Medicine, 2020)
A spaceflight has enormous influence on the health of space voyagers due to the combined effects of microgravity and cosmic radiation. Known effects of microgravity (μg) on cells are changes in differentiation and growth. Considering the commercialization of spaceflight, future space exploration, and long-term manned flights, research focusing on differentiation and growth of stem cells and cancer cells exposed to real (r-) and simulated (s-) μg is of high interest for regenerative medicine and cancer research. In this review, we focus on platforms to study r- and s-μg as well as the impact of μg on cancer stem cells in the field of gastrointestinal cancer, lung cancer, and osteosarcoma. Moreover, we review the current knowledge of different types of stem cells exposed to μg conditions with regard to differentiation and engineering of cartilage, bone, vasculature, heart, skin, and liver constructs.
CRIS-Team Scopus Importer:2020-05-12
Keywords: cancer stem cells; microgravity; multicellular spheroids; organoids; random positioning machine; rotating wall vessel; spaceflight; stem cells; tissue engineering

The impact of microgravity-based proteomics research - Grimm, Daniela; Pietsch, Jessica; Wehland, Markus; Richter, Peter; Strauch, Sebastian; Lebert, Michael; Magnusson, Nils Erik; Wise, Petra; Bauer, Johann (Expert Review of Proteomics, 2014)
Proteomics is performed in microgravity research in order to determine protein alterations occurring qualitatively and quantitatively, when single cells or whole organisms are exposed to real or simulated microgravity. To this purpose, antibody-dependent (Western blotting, flow cytometry, Luminex technology) and antibody-independent (mass spectrometry, gene array) techniques are applied. The anticipated findings will help to understand microgravity-specific behavior, which has been observed in bacteria, as well as in plant, animal and human cells. To date, the analyses revealed that cell cultures are more sensitive to microgravity than cells embedded in organisms and that proteins changing under microgravity are highly interactive. Furthermore, one has to distinguish between primary gravity-induced and subsequent interaction-dependent changes of proteins, as well as between direct microgravity-related effects and indirect stress responses. Progress in this field will impact on tissue engineering and medicine and will uncover possibilities of counteracting alterations of protein expression at lowered gravity. © 2014 Informa UK, Ltd.
Keywords: 3D cell growth; bed rest; clinostat; random positioning machine; spaceflight; tail suspension

The influence of microgravity on Euglena gracilis as studied on Shenzhou 8 - Nasir, Adeel; Strauch, Sebastian; Becker, Ina; Sperling, Anna; Schuster, Martin; Richter, Peter; Weißkopf, Matthias; Ntefidou, Maria; Daiker, Viktor; An, Y. A.; Li, X. Y.; Liu, Y. D.; et al. (Plant Biology, 2014)
The German Aerospace Center (DLR) enabled German participation in the joint space campaign on the unmanned Shenzhou 8 spacecraft in November 2011. In this report, the effect of microgravity on Euglena gracilis cells is described. Custom-made dual compartment cell fixation units (containing cells in one chamber and fixative - RNA lysis buffer - in another one) were enclosed in a small container and placed in the Simbox incubator, which is an experiment support system. Cells were fixed by injecting them with fixative at different time intervals. In addition to stationary experiment slots, Simbox provides a 1g reference centrifuge. Cell fixation units were mounted in microgravity and 1g reference positions of Simbox. Two Simbox incubators were used, one for space flight and the other as ground reference. Cells were fixed soon after launch and shortly before return of the spaceship. Due to technical problems, only early in-flight samples (about 40min after launch microgravity and corresponding 1g reference) were fully mixed with fixative, therefore only data from those samples are presented. Transcription of several genes involved in signal transduction, oxidative stress defence, cell cycle regulation and heat shock responses was investigated with quantitative PCR. The data indicate that Euglena cells suffer stress upon short-term exposure to microgravity; various stress-induced genes were up-regulated. Of 32 tested genes, 18 were up-regulated, one down-regulated and the rest remained unaltered. These findings are in a good agreement with results from other research groups using other organisms.
Keywords: Euglena gracilis; gene expression; microgravity; qPCR; space flight; unicellular flagellate

The involvement of a protein kinase in phototaxis and gravitaxis of Euglena gracilis - Daiker, Viktor; Häder, Donat-Peter; Richter, Peter; Lebert, Michael (Planta, 2011)
The unicellular flagellate Euglena gracilis shows positive phototaxis at low-light intensities (< 10 W/m(2)) and a negative one at higher irradiances (> 10 W/m(2)). Phototaxis is based on blue light-activated adenylyl cyclases, which produce cAMP upon irradiation. In the absence of light the cells swim upward in the water column (negative gravitaxis). The results of sounding rocket campaigns and of a large number of ground experiments led to the following model of signal perception and transduction in gravitaxis of E. gracilis: The body of the cell is heavier than the surrounding medium, sediments and thereby exerts a force onto the lower membrane. Upon deviation from a vertical swimming path mechano-sensitive ion channels are activated. Calcium is gated inwards which leads to an increase in the intracellular calcium concentration and causes a change of the membrane potential. After influx, calcium activates one of several calmodulins found in Euglena, which in turn activates an adenylyl cyclase (different from the one involved in phototaxis) to produce cAMP from ATP. One further element in the sensory transduction chain of both phototaxis and gravitaxis is a specific protein kinase A. We found five different protein kinases A in E. gracilis. The blockage of only one of these (PK.4, accession No. EU935859) by means of RNAi inhibited both phototaxis and gravitaxis, while inhibition of the other four affected neither phototaxis nor gravitaxis. It is assumed that cAMP directly activates this protein kinase A which may in turn phosphorylate a protein involved in the flagellar beating mechanism.
Keywords: Euglena; Gravitaxis; Phototaxis; Protein kinase; Signal transduction

Time Profile of Cosmic Radiation Exposure During the EXPOSE-E Mission: The R3DE Instrument - Dachev, Tsvetan; Horneck, Gerda; Haeder, Donat-Peter; Schuster, Martin; Richter, Peter; Lebert, Michael; Demets, Rene (Astrobiology, 2012)
The aim of this paper is to present the time profile of cosmic radiation exposure obtained by the Radiation Risk Radiometer-Dosimeter during the EXPOSE-E mission in the European Technology Exposure Facility on the International Space Station's Columbus module. Another aim is to make the obtained results available to other EXPOSE-E teams for use in their data analysis. Radiation Risk Radiometer-Dosimeter is a low-mass and small-dimension automatic device that measures solar radiation in four channels and cosmic ionizing radiation as well. The main results of the present study include the following: (1) three different radiation sources were detected and quantified-galactic cosmic rays (GCR), energetic protons from the South Atlantic Anomaly (SAA) region of the inner radiation belt, and energetic electrons from the outer radiation belt (ORB); (2) the highest daily averaged absorbed dose rate of 426 mu Gy d(-1) came from SAA protons; (3) GCR delivered a much smaller daily absorbed dose rate of 91.1 mu Gy d(-1), and the ORB source delivered only 8.6 mu Gy d(-1). The analysis of the UV and temperature data is a subject of another article (Schuster et al., 2012).
Keywords: Ionizing radiation; R3D; ISS

To Die or Not to Die: Cell Death in Biology and Disease - Krueger, Marcus; Richter, Peter (International Journal of Molecular Sciences, 2022)
CRIS-Team WoS Importer:2022-07-08

Using colistin as a trojan horse: Inactivation of gram-negative bacteria with chlorophyllin - Richter, Peter; Krüger, Marcus; Prasad, Binod; Gastiger, Susanne; Bodenschatz, Mona; Wieder, Florian; Burkovski, Andreas; Geißdörfer, Walter; Lebert, Michael; Strauch, Sebastian M. (Antibiotics, 2019)
Colistin (polymyxin E) is a membrane-destabilizing antibiotic used against Gram-negative bacteria. We have recently reported that the outer membrane prevents the uptake of antibacterial chlorophyllin into Gram-negative cells. In this study, we used sub-toxic concentrations of colistin to weaken this barrier for a combination treatment of Escherichia coli and Salmonella enterica serovar Typhimurium with chlorophyllin. In the presence of 0.25 µg/mL colistin, chlorophyllin was able to inactivate both bacteria strains at concentrations of 5-10 mg/L for E. coli and 0.5-1 mg/L for S. Typhimurium, which showed a higher overall susceptibility to chlorophyllin treatment. In accordance with a previous study, chlorophyllin has proven antibacterial activity both as a photosensitizer, illuminated with 12 mW/cm2, and in darkness. Our data clearly confirmed the relevance of the outer membrane in protection against xenobiotics. Combination treatment with colistin broadens chlorophyllin’s application spectrum against Gram-negatives and gives rise to the assumption that chlorophyllin together with cell membrane-destabilizing substances may become a promising approach in bacteria control. Furthermore, we demonstrated that colistin acts as a door opener even for the photodynamic inactivation of colistin-resistant (mcr-1-positive) E. coli cells by chlorophyllin, which could help us to overcome this antimicrobial resistance.
CRIS-Team Scopus Importer:2019-10-25
Keywords: Antibiotic resistance; Bacteria; Chlorophyll; Combination therapy; Mcr-1; Photosensitization

What an Escherichia coli Mutant Can Teach Us About the Antibacterial Effect of Chlorophyllin - Krueger, Marcus; Richter, Peter; Strauch, Sebastian; Nasir, Adeel; Burkovski, Andreas; Antunes, Camila A.; Meißgeier, Tina; Schlücker, Eberhard; Schwab, Stefan; Lebert, Michael (Microorganisms, 2019)
Due to the increasing development of antibiotic resistances in recent years, scientists search intensely for new methods to control bacteria. Photodynamic treatment with porphyrins such as chlorophyll derivatives is one of the most promising methods to handle bacterial infestation, but their use is dependent on illumination and they seem to be more effective against Gram-positive bacteria than against Gram-negatives. In this study, we tested chlorophyllin against three bacterial model strains, the Gram-positive Bacillus subtilis 168, the Gram-negative Escherichia coli DH5 alpha and E. coli strain NR698 which has a deficient outer membrane, simulating a Gram-negative "without" its outer membrane. Illuminated with a standardized light intensity of 12 mW/cm(2), B. subtilis showed high sensitivity already at low chlorophyllin concentrations (<= 10(5) cfu/mL: <= 0.1 mg/L, 10(6)-10(8) cfu/mL: 0.5 mg/L), whereas E. coli DH5 alpha was less sensitive (<= 10(5) cfu/mL: 2.5 mg/L, 10(6) cfu/mL: 5 mg/L, 10(7)-10(8) cfu/mL: ineffective at <= 25 mg/L chlorophyllin). E. coli NR698 was almost as sensitive as B. subtilis against chlorophyllin, pointing out that the outer membrane plays a significant role in protection against photodynamic chlorophyllin impacts. Interestingly, E. coli NR698 and B. subtilis can also be inactivated by chlorophyllin in darkness, indicating a second, light-independent mode of action. Thus, chlorophyllin seems to be more than a photosensitizer, and a promising substance for the control of bacteria, which deserves further investigation.
CRIS-Team WoS Importer:2019-03-15